2009
DOI: 10.1111/j.1365-2249.2009.03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between total immunoglobulin E and antibody responses to naturally acquired Ascaris lumbricoides infection and polymorphisms of immune system-related LIG4, TNFSF13B and IRS2 genes

Abstract: SummaryThe 13q33-34 region harbours a susceptibility locus to Ascaris lumbricoides, although the underlying genes are unknown. Immunoglobulin (Ig)E and IgG confer protective immunity and here we sought to investigate in an endemic population whether LIG4, TNFSF13B and IRS2 genes influence IgE and IgG levels against Ascaris and the ABA-1 allergen as a putative resistance marker. Mite-allergic asthmatic patients were analysed for potential relationships between Ascaris predisposition and allergy. One thousand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 55 publications
2
63
0
2
Order By: Relevance
“…Studies in humans and other mammals support the role of genetic factors in the predisposition to Ascaris [37,47] but few genes have been identified so far [43,[48][49][50][51]52•]. A summary of genes and genomic regions associated with the susceptibility to human ascariasis is presented in Table 1.…”
Section: Immunogenetics Of the Ige Responses To Ascaris And Allergensmentioning
confidence: 99%
“…Studies in humans and other mammals support the role of genetic factors in the predisposition to Ascaris [37,47] but few genes have been identified so far [43,[48][49][50][51]52•]. A summary of genes and genomic regions associated with the susceptibility to human ascariasis is presented in Table 1.…”
Section: Immunogenetics Of the Ige Responses To Ascaris And Allergensmentioning
confidence: 99%
“…According to the inclusion criteria, seven case-control studies Fu et al, 2003;Han et al, 2004;Lee et., al 2005;BCAC, 2006;GarciaClosas et al, 2006;Acevedo et al, 2009;Jakubowska et al, 2010) appeared to have met the inclusion criteria. The flow chart of study selection is shown in Figure 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Una característica de estos estudios es que los alelos de propensión a helmintiasis y de respuesta contra alérgenos se han investigado en poblaciones y ambientes diferentes, por lo que las conclusiones son indirectas en su mayoría (62)(63), limitación que se extiende a otras investigaciones sobre el tema que emplean métodos de bioinformática (64). En cambio, en un estudio reciente se observó, en una misma población expuesta a alérgenos de ácaros y A. lumbricoides, asociaciones de algunos alelos con la respuesta IgE contra A. lumbricoides, pero no con la dirigida a los ácaros (65).…”
Section: Respuesta Th2 Ante Moléculas Inocuas Como Los Alérgenosunclassified